Personal Accounts of Poverty: A Thematic Analysis of Social Media. Issue 6 (2nd November 2017) - Caplan, Mary A.; Purser, Gregory; Kindle, Peter A.
ABSTRACT: The field of social work seeks to enhance human well-being by addressing the needs of people living in poverty. Three billion people around the world use the internet daily, and 65% of them use social media. This article qualitatively identifies emergent themes about the lived experiences of poverty from people who reported either being poor or having have been poor, using selected social media posts ( N = 1, 495) on the website Reddit. We found that the experiences of poverty bring arduousness and hardship, which necessitates an arsenal of survival strategies and skills. It was also found that some people who were poor experienced the saving grace of unexpected charitable acts, which eased their burden. Moreover, these experiences manifest in vestigial feelings and behaviors even when one is no longer poor. An understanding of the lived experiences by poor people themselves is a foundational task for social work educators, practitioners, and researchers.